Pengaruh Debt to Equity Ratio dan Reputasi Auditor Terhadap Audit Report Lag dengan Profitabilitas Sebagai Pemoderasi - Rianto -; Dea Pebrianti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
This study aims to determine the effect of debt to equity ratio and auditor reputation on audit report lag. The measurement used for audit report lag, uses an ordinal scale, productivity is measured by total asset turnover, firm size is measured by total assets ln and maturity is measured by dummy variables. The population used in this study are all sukuk issued by non-financial companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sampling method used in this study was purposive sampling. The number of samples in this study were 90 samples of sukuk from 10 companies. The data analysis method used to test the hypothesis in this study is the ordinal logistic regression analysis method. The results showed that productivity had a significant positive effect on the sukuk rating, firm size had a significant positive effect on the sukuk rating and maturity had no significant effect on the sukuk rating